First European consensus for diagnosis, management, and treatment of transthyretin familial amyloid polyneuropathy - Adams, David; Suhr, Ole B.; Hund, Ernst; Obici, Laura; Tournev, Ivailo; Campistol, Josep M.; Slama, Michel S.; Hazenberg, Bouke P.; Coelho, Teresa (Current opinion in neurology, 2016)
Purpose of review - Early and accurate diagnosis of transthyretin familial amyloid polyneuropathy (TTR-FAP) represents one of the major challenges faced by physicians when caring for patients with idiopathic progressive neuropathy. There is little consensus in diagnostic and management approaches across Europe. - Recent findings - The low prevalence of TTR-FAP across Europe and the high variation in both genotype and phenotypic expression of the disease means that recognizing symptoms can be difficult outside of a specialized diagnostic environment. The resulting delay in diagnosis and the possibility of misdiagnosis can misguide clinical decision-making and negatively impact subsequent treatment approaches and outcomes. - Summary - This review summarizes the findings from two meetings of the European Network for TTR-FAP (ATTReuNET). This is an emerging group comprising representatives from 10 European countries with expertise in the diagnosis and management of TTR-FAP, including nine National Reference Centres. The current review presents management strategies and a consensus on the gold standard for diagnosis of TTR-FAP as well as a structured approach to ongoing multidisciplinary care for the patient. Greater communication, not just between members of an individual patient's treatment team, but also between regional and national centres of expertise, is the key to the effective management of TTR-FAP.
Gesehen am 03.08.2020